The Effect of Agility on Firm Performance: Study in Indonesian Aviation Industry During Covid-19 Pandemic - Aviva Salsabila Caesari; Iqbal, Muhammad; Hutahayan, Benny (Profit: Jurnal Adminsitrasi Bisnis, 2023)
Business competition during the Covid-19 pandemic has become a crucial topic of discussion because many economic sectors have experienced paralysis, including the aviation industry. This situation encourages each company to adapt to the business and dynamics in its environment to maintain its performance. This study was conducted to test and analyze the influence of strategic agility, market capitalizing agility, and operational agility adjustments on firm performance. The methods include quantitative research methods with PLS-SEM. This research found that strategic and market capitalizing agility affect a firm's performance. Differences in the company's business operations can affect the company's performance which is also supported by dynamics in the business environment.